A Method for Modeling Time Delay-Related Measurement Errors, Applicable in Power and Energy Monitoring and in Fault Detection Algorithms for Energy Grids - Marian Kampik; Łukasz Dróżdż; Jerzy Roj (Energies, 2025)
This paper presents a proposed error model for the signal errors resulting from delays in the measurement chain. The analysis focuses on the uncertainty budget of the input quantities in the digital signal-processing algorithm, examining the influence of delays in the analog-to-digital processing stage on the uncertainty of these quantities. A classification of delays, based on their properties and the nature of the error signal they generate, is proposed. In addition to the mathematical model and its verification through the Monte Carlo method, the paper discusses potential applications of the proposed analysis method for selected implementations of measurement chains. This method can be utilized for power and energy measurement, power grid fault detection, and the identification of short circuits, among other applications.